PESAN KESETARAAN PENYANDANG DISABILITAS MELALUI INTERAKSI SIMBOLIK MEDIA SOSIAL - Putra, Rizki Saga; Marpaung, Yuni Novianti Marin; Pradhana, Yudha; Rimbananto, Muhammad Ramelan (Interaksi: Jurnal Ilmu Komunikasi, 2021)
Being considered equal to normal people in general is a dream that people with disa-bilities really want to realize. The public's view of disability has constructed the stig-ma that people with disabilities are unable to move like normal people specifically relating to physical exercise.. The difficulty of dismantling the stigma that is already inherent and generalizing persons with disabilities with physical disability or mal-function becomes a particular challenge faced by persons with disabilities as a mi-nority group. This paper uses the constructivist paradigm as a point of view in look-ing at understanding the complexity of social construction. The phenomenological method used in this study will explore the perspective of individuals with disabilities through self-concept "me" as an object that is the result of community construction, try to be replaced with "I" as a subject that is reconstructed through the help of so-cial media with self-actualization amid physical limitations which is owned. This study found that messages through social media that contain hopes and big dreams which imply that people with disabilities also have physical abilities and expertise equivalent to normal people in general. Various attempts were made, even more so by utilizing social media as a means of proving to the world about "This Is Me"and “I Can Do Anything